Efforts to Increase Patient Loyalty to Hospitals: A Scoping Review - Gazali Gafar; Luky Dwiantoro; Fitria Handayani (Indonesian Journal of Global Health Research, 2025)
Patient loyalty of some hospitals is at low and medium levels. Hospitals develop strategies to increase patient loyalty. Objective to provide a complete overview of the factors that affect patient loyalty and strategies to improve patient loyalty. This method of scoping review reviewed literature published between 2020 dan 2025 with sources from the Pubmed, ScinceDirect dan Scoupas database. The include studies involved research related to ptient loyalty in hospitals. Focusing on the various strategies and efforts used to increase patient loyalty. From the results of literature search using the Population, Concept, Context (PCC) approach in the PubMed and ScienceDirect databases, with the keywords 'Effort to Increase AND Loyalty', 'Hospital OR Healthcare', and 'Patient AND Loyalty', 1,246 articles were obtained. After going through the identification and selection process using the PRISMA-ScR flow, 12 articles were selected that met the criteria and were used in this study. There are various factors that increase patient loyalty, lncluding: quality of service, patient satisfaction, trust, adn interpersonal relationships between healtcare workers and patients. In addition, there are also various strategies to increase patient loyalty, such as patient-oriented services, improving the skills of helath workers, and the use of information technology. Increasing patient loyalty in hospitals requires a holistic approach, including: information technology, human reasources, quality management and interpersonal between healthcare workers and patiens.